2003
DOI: 10.1111/j.1463-6409.2004.00137.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the nervous system in Paraphanostoma (Acoela)

Abstract: Evolution of the nervous system in Paraphanostoma (Acoela). -Zoologica Scripta, 33 , 71-88. According to recent molecular studies, the Acoela are the earliest extant bilaterian group. Their nervous system displays a striking variety of patterns. The aim of the present investigation was to study the variability of the nervous system in a monophyletic group of the Acoela. Six species of Paraphanostoma were chosen for the study. Using immunocytochemical methods and confocal scanning laser microscopy, the immunore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 30 publications
4
78
0
1
Order By: Relevance
“…The phylum Xenacoelomorpha is formed of animals with a relatively simple morphology, including that of their nervous systems (Raikova et al, 2000a;Raikova et al, 2000b;Raikova et al, 2004a;Raikova et al, 2004b;Achatz et al, 2013). Here, and for the first time using the genome sequence of members of this group, we have undertaken a systematic study of two superfamilies, the bHLHs and GPCRs, involved in the specification and the functionality of nerve tissue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The phylum Xenacoelomorpha is formed of animals with a relatively simple morphology, including that of their nervous systems (Raikova et al, 2000a;Raikova et al, 2000b;Raikova et al, 2004a;Raikova et al, 2004b;Achatz et al, 2013). Here, and for the first time using the genome sequence of members of this group, we have undertaken a systematic study of two superfamilies, the bHLHs and GPCRs, involved in the specification and the functionality of nerve tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The Acoelomorph nervous system is a pertinent case here because it shows a high degree of variability within the group. It is characterized, according to some authors, by a low degree of centralization in the anterior domain (Raikova et al, 2004a;Hejnol and Martindale, 2008;Raikova, 2008). In the past 10 years, several studies using electron microscopy and immunocytochemistry have added to our knowledge of acoel neuroanatomy.…”
Section: The Acoel Nervous System In Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…The nervous system, like cnidarians, is located basiepidermally, although in some acoel species nerve fibres are located subepidermally (Rieger et al 1991;Raikova et al 1998Raikova et al , 2004, and is connected to photoreceptive cells ('eyes') and epidermal sensory cells. Thus, if acoelomorphs resemble the urbilaterian, a dorsally or ventrally centralized nervous system is not part of the ground pattern of the Bilateria.…”
Section: The Phylogenetic Position Of the Acoelomorpha And Their Impamentioning
confidence: 99%
“…Even closely related species display noticeably different NS organization: for instance, Faerlea glomerata Westblad, 1945 has a superficial weak barrel-shaped 5-HT immunoreactive (IR) brain (we follow the terminology suggested by Richter et al (2010)), while its close relative Avagina incola Leiper, 1902 displays a deep concentrated bridgeshaped brain (Reuter et al 2001b). The acoel NS variability was further demonstrated by the examination of seven representatives of Childiidae, a group of Acoela for which there is strongly corroborated phylogenetic hypothesis (Raikova et al 2004b). The study demonstrated that the brains in childiid species, although diverse in detail, still follow the same general pattern, and the complexity of this pattern progressively increases in accordance with the phylogenetic tree.…”
Section: Introductionmentioning
confidence: 89%